UJI TINGKAT KEBAKUAN TES KETERAMPILAN TENDANGAN PADA CABANG OLAHRAGA PENCAK SILAT - Ramdani Amrullah (Jurnal Pendidikan Olah Raga, 2012)
Advancement of science and technology in various fields of sports experts create incentives for each sport to develop the sport through a planned and orderly development in order to achieve a high achievement. One of the obtacles that have in sports coaching is a way or method for determining a potential athlete. Various ways have been carried out to select athletes based on the observation of elections, so can not give a clear picture of the right or the ability af martial arts athletes. Formulation of gauge for the ability to kick in sport martial arts are important and urgent in a range of sports coaching martial arts itself. This relates to the data retrieval process of coaching and training as a cornerstone in the evaluation results of the exercise.Based on the results of data processing and analysis, the conclusions from the results of this study are as follows: The test of skills in the sport of martial arts kicks distance of 70 cm with a time of 5 seconds has a level of significant validitas and reliability. This is indicated by  a value of 0.78 for test validity and reliability tests of 0.96. Significance tests of the validity of test results showed t count = 41.50 and reliability test showed t count = 1.78 is greater than t-table with a significance level = 1.77 = 0.05 and df = 13. The conclusion is the second test showed significant results.